Assessment of Nurses' Knowledge Toward Providing Nursing Care to Patients with Hemodialysis at Baghdad Teaching Hospital - Mahmood , Wurood A.; Hussein , Basim Hasson (Medical Science Journal for Advance Research, 2025)
Background: The most prevalent treatment for the disease known as chronic renal failure (CRF), which is on the rise worldwide, is hemodialysis. The most popular technique for treating severe and irreversible renal failure is hemodialysis. Objective(s): The purpose of this study had been assessing nurses' knowledge of nursing care for hemodialysis patients and to determine the association between sociodemographic characteristics and nurses, including age, marital status, educational attainment, number of years of experience in hemodialysis units, and participation in training sessions related to nursing care in hemodialysis. Methods: A descriptive study was conducted at the Baghdad Teaching Hospital's hemodialysis units from October 25, 2022, until April 2, 2023. From Baghdad Teaching Hospitals, a non-probability purposive sample of fifty nurses employed in hemodialysis units was chosen. Using a developed questionnaire with two sections—a demographic data form with five items and a questionnaire about nurses' knowledge with twenty items—the data was gathered through direct interviewing. Pilot research was used to assess the questionnaire's reliability, and a panel of seven experts evaluated its validity. The data was analyzed using inferential statistical analysis techniques (Chi-square) and descriptive statistical techniques (frequency, percentage, and score mean). Results: According to the study's findings, half of the sample was female, most of them were high school graduates, and they were all in their 20s to 29s. According to the study, nurses' understanding of providing nursing care to patients undergoing hemodialysis was inadequate. The study demonstrated a significant relationship between gender, level of education, years of experience in hemodialysis units, and participation in training sessions, and nurses' knowledge regarding nursing care. Based on the researcher's point of view, these findings mean the hemodialysis units are totally depends on nurses who have graduated from secondary nursing school and nursing institute, while nurses who have graduated from nursing college are assigned to special units and are still in limited numbers relative to other nurses. Regarding the level of education, based on the researcher's point of view, these results suggest that the fact that there is a recurrent rotation from one unit to another within the hospital might explain the few years of nursing experience in hemodialysis units. On the other hand, when nurses are young, the outcome explained would have a greater willingness to improve their skills and practices relative to other nurses in the higher age group. Regarding the participation in session about nursing care in hemodialysis, based on the researcher point of view, all nursing staff in hemodialysis units should be enrolled in training sessions to enhance their nursing care awareness and skills. This may be due to their hospital emphasis on courses related to infection prevention rather than dialysis related Conclusion: According to the study, nurses' knowledge of nursing care was significantly correlated with their gender, educational attainment, years of experience in hemodialysis units, and sharing during training sessions.